PENGARUH PROFITABILITAS DAN INVESTMENT OPPORTUNITY SET TERHADAP KEBIJAKAN DIVIDEN DENGAN LIKUIDITAS SEBAGAI PEMODERASI - Ni Luh Gede Intan Sri Devi; Ni Ketut Muliati (UNHI Press, 2019)
The company's dividend policy has an important influence on many parties involved in the community. For shareholders or investors, cash dividends are the rate of return on their investment with share ownership issued by the company, but management, cash dividends are cash outflows that reduce the company's cash. The purpose of this study was to determine the effect of profitability, investment opportunity set on cash dividend policy and to determine the effect of liquidity as a moderating variable between profitability and investment opportunity set against cash dividend policy.This research was conducted at a banking company registered on the Stock Exchange with a 5-year observation period, namely from 2011-2015. Data analysis techniques use moderated regression analysis (MRA). The results showed that Profitability and Investment opportunity set had an effect on the cash dividend policy. Liquidity can moderate the relationship between Profitability and Investment opportunity set against world dividend policy.